2017
DOI: 10.1111/echo.13488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular function in preterm infants with bronchopulmonary dysplasia using various echocardiographic techniques

Abstract: E/A and E/E' ratios are the most sensitive indicators of impaired left ventricle diastolic function in preterm infants with bronchopulmonary dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Although we included neonates with and without bronchopulmonary dysplasia in our current study, we did not expect the dysplasia to affect MPI values in preterm neonates because LV MPI did not differ between preterm neonates with or without bronchopulmonary dysplasia in our previous study. 11 In this study, FS%, an indicator of systolic function, was lower in preterm neonates at week 40 of PCA than in term neonates after PDA closure and on the 28th day of life. However, we suspect that the decreased FS% in preterm neonates did not indicate impaired systolic function because other indicators of systolic function in preterm neonates (S´ wave, MPI) were not impaired in these children.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Although we included neonates with and without bronchopulmonary dysplasia in our current study, we did not expect the dysplasia to affect MPI values in preterm neonates because LV MPI did not differ between preterm neonates with or without bronchopulmonary dysplasia in our previous study. 11 In this study, FS%, an indicator of systolic function, was lower in preterm neonates at week 40 of PCA than in term neonates after PDA closure and on the 28th day of life. However, we suspect that the decreased FS% in preterm neonates did not indicate impaired systolic function because other indicators of systolic function in preterm neonates (S´ wave, MPI) were not impaired in these children.…”
Section: Discussionsupporting
confidence: 42%
“…Moreover, MPI did not improve significantly in preterm neonates 4 weeks after birth (0.36). 14 Similarly, in a study by Hirose et al, 11 MPI was similar in preterm neonates at week 40 of PCA and term neonates measured on the 28th day of life (0.44 vs 0.43, respectively). Although we included neonates with and without bronchopulmonary dysplasia in our current study, we did not expect the dysplasia to affect MPI values in preterm neonates because LV MPI did not differ between preterm neonates with or without bronchopulmonary dysplasia in our previous study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…1,[21][22][23] Previous echocardiography studies have found BPD to have a detrimental impact on cardiac function at or near term corrected gestational age, 4,6,7,12,24-26 early infancy 5,8,11,13,14 and school age. 27 Most studies have found alterations in RV function 4,6,7,[11][12][13][14]24 while few have performed prospective longitudinal echocardiography analysis 4,12,13,26 or have examined LV function. 5,8,26 Due to the presence of ventricular interactions it is relevant to include a biventricular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…During the neonatal time frame, a number of studies have described an association between cardiac dysfunction and BPD. While some report improvement in cardiovascular findings in BPD over time, 46 others demonstrate both right and left ventricular dysfunction with severity of cardiac dysfunction correlated with the severity of BPD 47,48 . However, in one study early cardiac dysfunction in preterm infants, in particular left ventricular dysfunction, was associated with the future development of BPD.…”
Section: Early Postnatal Relationships Between Prematurity Bpd and Cardiovascular Diseasementioning
confidence: 96%